Arrestin recognizes GPCRs independently of the receptor state - Ivana Petrovic; Meltem Tatli; Samit Desai; Anne Grahl; Dongchun Ni; Henning Stahlberg; Anne Spang; Stephan Grzesiek; Layara Akemi Abiko (Proceedings of the National Academy of Sciences, 2025)
Only two nonvisual arrestins recognize many hundreds of different, intracellularly phosphorylated G protein-coupled receptors (GPCRs). Due to the highly dynamic nature of GPCR•arrestin complexes, the critical determinants of GPCR–arrestin recognition have remained largely unclear. We show here that arrestin2 recruitment to the β 1 -adrenergic receptor (β 1 AR) can be induced by an arrestin-activating phosphopeptide that is not covalently linked to the receptor and that the recruitment is independent of the presence and type of the orthosteric receptor ligand. Apparently, the arrestin–receptor interaction is driven by the conformational switch within arrestin induced by the phosphopeptide, whereas the electrostatic attraction toward the receptor phosphosites may only play an auxiliary role. Extensive NMR observations show that in contrast to previous static GPCR•arrestin complex structures, the β 1 AR complex with the beta-blocker carvedilol and arrestin2 is in a G protein-inactive conformation. The insensitivity to the specific receptor conformation provides a rationale for arrestin’s promiscuous recognition of GPCRs and explains the arrestin-biased agonism of carvedilol, which largely blocks G protein binding, while still enabling arrestin engagement.